Being different in public. Issue 5 (2nd September 2016) - Hickey-Moody, Anna
Abstract: In this article, the phrase 'being different in public' is used to think about people with disabilities in public culture. I argue for the cultural value of disability in an era of austerity arguably marked by an ableism that pushes people to 'pass' as not disabled. Such a lack of cultural value is remedied through the work of Disability Arts organizations, and I take the work of a British and an Australian Dance Theatre company as two of many possible examples in which arts practices change public culture through staging the work of performers with disability. In building this argument, I develop a feminist, queer methodology for reading Deleuze and Guattari and Butler as theorists of public culture. Specifically, as theorists that illustrate the cultural significance of being different in public. Reading Butler and Deleuze together can teach us to appreciate lack as a mode of aesthetic refusal, as a way of being obviously different, or 'positively negative' in public culture. I take Deleuze and Guattari and Butler as part of the same intellectual public, a community concerned with creative cultural interventions into normative identity politics. I consider integrated dance practice through this framework as a valuable political and public intervention. Integrated dance is a term used to describe dance that brings together people with and without a disability. I argue that disability can be felt and configured differently through performance. The aesthetics of reimagining what a disabled body can do, or what a dancing body should be, not only constitute a practice of aesthetic activism but an aesthetic refusal of dominant body ideologies and capitalist codings of dance.